2004
DOI: 10.1016/j.febslet.2004.09.075
|View full text |Cite
|
Sign up to set email alerts
|

Islet amyloid polypeptide‐induced membrane leakage involves uptake of lipids by forming amyloid fibers

Abstract: Fibril formation of islet amyloid polypeptide (IAPP) is associated with cell death of the insulin-producing pancreatic bcells in patients with Type 2 Diabetes Mellitus. A likely cause for the cytotoxicity of human IAPP is that it destroys the barrier properties of the cell membrane. Here, we show by fluorescence confocal microscopy on lipid vesicles that the process of hIAPP amyloid formation is accompanied by a loss of barrier function, whereby lipids are extracted from the membrane and taken up in the formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
274
1
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 246 publications
(309 citation statements)
references
References 20 publications
21
274
1
10
Order By: Relevance
“…Previous studies have shown that the N-terminal 1-19 region, rather than the amyloidogenic 20-29 region, is primarily responsible for the interaction of the IAPP peptide with membranes. Liposome leakage experiments presented in this study confirm that the pathological membrane disrupting activity of the full-length hIAPP is also shared by hIAPP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . The hIAPP 1-19 fragment at a low concentration of peptide induces membrane disruption to a near identical extent as the full-length peptide.…”
supporting
confidence: 63%
See 4 more Smart Citations
“…Previous studies have shown that the N-terminal 1-19 region, rather than the amyloidogenic 20-29 region, is primarily responsible for the interaction of the IAPP peptide with membranes. Liposome leakage experiments presented in this study confirm that the pathological membrane disrupting activity of the full-length hIAPP is also shared by hIAPP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . The hIAPP 1-19 fragment at a low concentration of peptide induces membrane disruption to a near identical extent as the full-length peptide.…”
supporting
confidence: 63%
“…The hIAPP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and hIAPP [20][21][22][23][24][25][26][27][28][29] peptides were synthesized using standard FMOC (9-fluornylmethoxycarbonyl) methods. A PAL-PEG resin was used to provide an amidated C-terminus.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations